2017
DOI: 10.1109/tbme.2016.2602228
|View full text |Cite
|
Sign up to set email alerts
|

Closed-Loop Prevention of Hypotension in the Heartbeating Brain-Dead Porcine Model

Abstract: The purpose of this paper is to demonstrate feasibility of a novel closed-loop controlled therapy for prevention of hypertension in the heartbeating brain-dead porcine model. Methods: Dynamic modeling and system identification were based on in vivo data. A robust controller design was obtained for the identified models. Disturbance attenuation properties, and reliability of operation of the resulting control system, were evaluated in vivo. Results: The control system responded both predictably and consistently… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1

Relationship

5
3

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 26 publications
0
6
0
Order By: Relevance
“…To investigate feasibility of the proposed algorithm, it was evaluated on data collected during the first of two experiments, reported in [14]. Diastolic, y d , and systolic, y s , values of a one hour section of arterial blood pressure data, sampled at 100 Hz, is shown in Figure 4a.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…To investigate feasibility of the proposed algorithm, it was evaluated on data collected during the first of two experiments, reported in [14]. Diastolic, y d , and systolic, y s , values of a one hour section of arterial blood pressure data, sampled at 100 Hz, is shown in Figure 4a.…”
Section: Discussionmentioning
confidence: 99%
“…The data was acquired as part of a closed-loop hemodynamic stabilization project. Experimental conditions and compliance with ethical standards were reported in [14]. Details concerning study ethics are additionally found at the end of this paper, under "Compliance with ethical standards".…”
Section: Robust Computation Of Pulse Pressure Variationsmentioning
confidence: 99%
“…A pressure transducer (DTX Plus, Argon Medical Devices, Frisco, USA) was connected to two narrow channels in the wall of the Boussignac tube through air-filled plastic tubing with non-flexible walls to measure intratracheal pressure. The transducer signal was recorded by a data aquisition system described in [17]. Due to the low-pass filtering effect of air in the pressure measurement tubes in [8], time-averaged maximum, mean, and minimum intratracheal pressure are used for comparison rather than real-time P trachea .…”
Section: B Experimentsmentioning
confidence: 99%
“…Individual catheters (Secalon-T-over-needle central venous catheter, 16G/1.70.130mm) for blood gas samples were inserted via direct puncture into the right carotid artery and right internal jugular vein. Catheters were also inserted into the ascending aorta and the right atrium for continuous invasive blood pressure measurement and connected to a data acquisition system (DAQ) described in [9]. A flow sensor (REF 6710; Novametrix Medical Inc., Wallingford, CT) was fitted to the proximal end of the Boussignac tube and connected to the same DAQ.…”
Section: Protocolmentioning
confidence: 99%